2011
DOI: 10.1111/j.1600-0722.2011.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of all three calbindins from a calcium‐ferry role in rat enamel cells

Abstract: It is widely accepted that healthy enamel formation depends on a steady supply of calcium, yet only fragmentary understanding exists about the mechanisms underlying transepithelial calcium transport. Several lines of evidence indicate that calcium principally follows a transcellular route, which classically is thought to be facilitated by cytosolic calcium-binding proteins termed calbindins. In enamel cells, however, this 'calcium-ferry' dogma appears to fail as we previously found that the major calbindin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
(162 reference statements)
0
18
0
Order By: Relevance
“…However, Hubbard et al [22] found that calretinin was primarily expressed during the differentiation stage of enamel formation, and only a faint calretinin band was observed at secretion stage while no such band was detectable during maturation. Based on these findings, the authors suggest retirement of the calcium ferry dogma from enamel biology—in murine models at least.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hubbard et al [22] found that calretinin was primarily expressed during the differentiation stage of enamel formation, and only a faint calretinin band was observed at secretion stage while no such band was detectable during maturation. Based on these findings, the authors suggest retirement of the calcium ferry dogma from enamel biology—in murine models at least.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various calcium-handling proteins were found to be up-regulated ~ 3-fold relative to the secretion phase, closely paralleling the increased calcium flux at maturation (Hubbard, 2000). However, contradicting the "calbindin ferry" dogma long held by the calcium-transport field (based largely on studies of gut and kidney), the major calbindin (Calb1/CB28) was found to be down-regulated during maturation, CB28-null mice lacked the dental phenotype, and the other 2 types of calbindin (Calb2 and S100g) were recently ruled out as alternative calcium transporters (Turnbull et al, 2004;Hubbard et al, 2011). Instead of a cytosolic transport mechanism, the biochemical data invoked an organellar route involving endoplasmicreticulum-related calcium stores (ER/Ca stores).…”
Section: Calcium Transportmentioning
confidence: 99%
“…; Hubbard et al . ). For calbindin 9kDa, immunolocalization, radioimmunoassay and mRNA analysis showed higher levels during the maturation stage (Table ) (Taylor et al .…”
Section: Introductionmentioning
confidence: 97%
“…In enamel cells, calretinin is expressed during the differentiation stage when generalized epithelial cells become pre‐ameloblasts but no data have been reported for secretory or maturation stages (Hubbard et al . ). Mutations to calretinin do not appear to have a major impact in enamel as no dental phenotypes have been reported.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation